Mercy Killing in Bioethical, Legal, and End-of-Life Care Perspectives - Reza Ahda Kadir (Punggawa Law Review, 2026)
Mercy killing remains a highly contested issue in bioethics, medical law, and end-of-life care because it involves the deliberate ending of life under the justification of compassion. Although the term is often associated with euthanasia and assisted dying, it must be carefully distinguished from refusal of treatment, withdrawal of life-sustaining treatment, do-not-resuscitate decisions, and palliative sedation, since these practices differ in intention, causation, consent, and legal consequences. This study aims to analyze mercy killing from bioethical, legal, and end-of-life care perspectives, with particular attention to patient autonomy, human dignity, vulnerability, palliative care, professional conscience, and implications for the Indonesian health-care context. Using a normative bioethical and legal-analytical approach, this article examines the ethical tension between relieving unbearable suffering and protecting human life. The analysis shows that autonomy cannot be separated from decision-making capacity, freedom from coercion, adequate information, and access to meaningful alternatives, especially palliative care. It also emphasizes that vulnerable groups, including older persons, disabled individuals, economically disadvantaged patients, and people with mental disorders, require stronger protection against subtle social pressure. In Indonesia, where law, religion, culture, and medical ethics strongly emphasize the sanctity and protection of life, the central priority should not be the normalization of active life-ending practices, but the strengthening of palliative care, legal clarity, clinical ethics consultation, and humane communication at the end of life.